Evaluasi Kinerja Keuangan dan Oprasional Usaha di Pondok Pesantren - Maulal Akmal, M Izzu; M. Masrukhan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
operational sustainability. This study aims to evaluate the financial and operational performance of business enterprises at Imam Syafi'i Islamic Boarding School, Brebes, Central Java. A qualitative research method with a case study approach was employed. Data collection techniques included observations, in-depth interviews, and document analysis of financial and operational records. The findings indicate that the boarding school has managed various Sharia-based businesses, such as agriculture, livestock, and small-scale enterprises. Despite increased revenue from these businesses, challenges remain, including a lack of transparency in financial recording and limited human resources in business management. This study recommends improving Sharia-based financial recording systems, strengthening the capacity of business managers, and diversifying enterprises to enhance the economic sustainability of the boarding school. Keywords: Performance Evaluation, Islamic Boarding School Finance, Sharia Business, Economic Management, Case Study